Biochemical, Physico-Chemical and Microbiological Properties of Camel Raw Milk Marketed in Bechar city (South-West Algeria): Hygienic and Safe Consumers Approach (Microbes and Health, 2016)
This study focused on the analysis of twenty-four samples of camel raw milk commercialized at the market of Bechar city. Sample analysis of raw milk was performed by measuring of some physicochemical parameters which the average results obtained have a slightly acidic pH (5.67), high titratable acidity (4.49g/l). Density, total dry extract and fat content were low (1.0268; 89g/l and 29.87g/l respectively), a lactose content of (28.18 g/l). The microbiological examination has several microbial quality attributes such as total bacteria, thermo tolerant coliforms, fecal Streptococci, Sulphite-reducing clostridia and fungal flora with average obtained 3.1 x 107 cfu/ml, 4.9 x 104 cfu/ml, 1.16 x 10 germ/ml, less than 5 spore/20ml and 2.36 x 103 uf/ml respectively. In addition, the analysis revealed the presence of coagulase positive Staphylococci for two samples, however, all samples are free of Salmonella sp. and Shigella sp. 58% of the samples were of satisfactory quality, 8.33% are acceptable and 33.33% are unacceptable.Microbes and Health, January 2015. 4(1): 14-18